INTERAKSI SOSIAL ORANG LANJUT USIA DENGAN ANGGOTA KELUARGA - Murlis Murlis (Ensiklopedia Social Review, 2019)
An interaction process is based on various factors, among others, factors of imitation, suggestion, identification and sympathy. The meeting between the children and parents is manifested in the form of visiting each other, that is, from time to time the child visits them or vice versa, the parents visit the child and miss their grandchildren at the same time. In this context there is an increase in mobility carried out by the elderly which can affect the degree or level of their health. Most of their children who are outside the kelurahan, namely 42.85% reside / live outside the district. In this connection, parents in old age make a visit (anjang ada). This means that in old age there is still population mobility. The mobility of the population in old age carries risks not only to the economy but also to health and safety because in old age the physical condition has decreased and is susceptible to disease. Most, namely around 71.42% of informants in the last year stated that they had been sick and only 28.57% stated that they had never been sick. For those who claim that they have been sick more than once with different types of disease.